PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERMUATAN KEARIFAN LOKAL TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA DI SD GUGUS I KECAMATAN BULELENG - Luh Candra Dewi; I Putu Suardipa; I Made Ari Winangun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model containing local wisdom on the creative thinking skills of fifth-grade students in mathematics at SD Gugus I, Buleleng District. The low ability of students to express ideas and find alternative solutions is the background of this research. The research method used is a quasi-experimental method with a Posttest-Only Control Group Design. The population consisted of all fifth-grade students totaling 215 students. The sample was selected using the equivalence test technique, determining one experimental class and one control class. Data collection was carried out using an essay test instrument to measure creative thinking skills which had been tested for validity and reliability. Data analysis used descriptive statistics and inferential statistics with t-test. The results showed that the average score of creative thinking skills in the experimental class was higher than the control class. Based on the hypothesis test, the value of t_count > t_table with a significance value <0.05, so H0 is rejected and H1 is accepted. It can be concluded that there is a significant effect of the CTL model containing local wisdom on students' creative thinking skills. This model encourages students to learn through real experiences linked to local culture, so that learning becomes meaningful and can optimize fluency, flexibility, originality, and elaboration in thinking.